Analisis Coefficient of Performance (COP) dengan Pemanfaatan Energi Panas Discharge Kompresor Sistem Heat Exchanger Double Tube pada AC 1 PK untuk Pemanas Air - Atifah, Nailul; Riyana, Angga; Astuti, Fifit (Jurnal Teknik Mesin, 2025)
Hot water has become an important part of everyday life. Utilization of waste heat is increasingly relevant in the modern era, due to very significant technological advances. One of them is the refrigeration system which regulates temperature by transferring heat energy from inside to outside the room. Basically, this heat can be used to heat water by absorbing heat before it reaches the condenser. Reusing waste heat from the condenser can save the electricity needed to heat water, making it an efficient way to utilize wasted energy. This research aims to determine the effect of variations in HE (heat exchanger) pipe length on the performance of the Coefficient of Performance COP, and the required electrical power consumption using heat exchanger calculation analysis for the CoolPack application. This research uses an experimental method on a 1 PK split AC with variations without a heat exchanger and with a 3 pass, 5 pass double tube heat exchanger. The results of this research show that without a heat exchanger the average COP is 3.68 and the electric power is 0.063 kWh, with a 3 pass heat exchanger the average COP is 4.1 with an increase of 11.4% from the data without using a heat exchanger and an electric power of 0.054 kWh, with a 5 pass heat exchanger the average COP is 4.66 with an increase of 26.6% from the data without using a heat exchanger and an electric power of 0.052. kWh. This shows that the better the heat dissipation in the condenser, the greater the heat absorbed by the evaporator, making the COP higher and the compressor work lower. Therefore, the use of electrical power is lower and the performance of an Air Conditioning system is more efficient.